A Mechanism for the Adsorption of 2-(Hexadecanoylamino)Acetic Acid by Smithsonite: Surface Spectroscopy and Microflotation Experiments - Bin Luo (Minerals, 2018)
Zinc is mostly extracted from oxidized zinc and zinc sulfide minerals, and this process involves flotation as a key step. While it is easier to float the sulfide mineral, its consumption and depletion has led to an increased reliance on oxidized zinc minerals, including smithsonite. Hence, the development of efficient ways of collecting smithsonite by flotation is an important objective. Herein, we describe the use of 2-(hexadecanoylamino)acetic acid (HAA), a novel surfactant, as a collector during smithsonite flotation. The mechanism and flotation performance of HAA during smithsonite flotation was investigated by total organic carbon (TOC) content studies, zeta potential measurements, Fourier-transform infrared (FTIR) spectroscopy, and X-ray photoelectron spectroscopy (XPS) analyses, combined with microflotation experiments. The flotation results revealed that HAA was an excellent collector in pulp over a wide pH range (9–12) and at a relatively low concentration (2 × 10−4 mol/L), at which a recovery of close to 90% of the smithsonite mineral was obtained. TOC content studies revealed that the good flotation recovery was ascribable to large amounts of collector molecule adsorbed on the smithsonite surface, while zeta potential measurements showed that the HAA was chemically adsorbed onto the smithsonite. FTIR and XPS analyses revealed that the HAA collector molecules adsorbed onto the smithsonite surface as zinc–HAA complexes involving carboxylate moieties and Zn sites on the smithsonite surface in alkaline solution.